OVERSEAS JAVANESE: DETERMINING A GOOD DAY TO GET MARRIED - Hakim , Anwar; Muhammad Hakiki, Kiki (LPPM UIN Sulthan Thaha Saifuddin Jambi, 2023)
Indonesian people are very famous for their customs and culture. In all aspects of life, whether related to worship rituals or any muamalah ritual, it is very closely related to customs that have existed for generations passed down by the ancestors of the Indonesian nation. Especially the Javanese people who are very close to the customs and culture that they have embraced. As an example of a custom that is still maintained today is to determine a good day to hold a marriage contract using the method of calculating the market day related to the birthday (weton) of the prospective bride and groom. This is when it is associated with marriage in Islam, it often causes polemics related to the law of determining the auspicious day of marriage based on the Javanese calculation formula.